2023
DOI: 10.3390/diagnostics13122047
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding Characteristics of Birt–Hogg–Dube Syndrome in Korea

Abstract: Birt–Hogg–Dube (BHD) is a rare genetic disorder characterized by multiple lung cysts, typical skin manifestations, and renal tumors. We prospectively enrolled thirty-one subjects from four South Korean institutions with typical lung cysts, and next-generation sequencing was conducted. We prospectively enrolled thirty-one subjects from four Korean institutions with typical lung cysts. Next-generation sequencing was performed to investigate mutations in the following genes: FLCN, TSC1, TSC2, CFTR, EFEMP2, ELN, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…This study investigated nine Korean patients with BHDS, with a mean diagnosis age of 49.2±18.2 years, consistent with previous Korean studies [5,9]. The rates of pulmonary cysts (86%), renal cancer (22%), and skin lesions (38%) were similar to those reported in earlier studies on Korean patients with BHDS [9,18].…”
supporting
confidence: 87%
“…This study investigated nine Korean patients with BHDS, with a mean diagnosis age of 49.2±18.2 years, consistent with previous Korean studies [5,9]. The rates of pulmonary cysts (86%), renal cancer (22%), and skin lesions (38%) were similar to those reported in earlier studies on Korean patients with BHDS [9,18].…”
supporting
confidence: 87%
“…One group demonstrated the compensation of LTBP4 for the loss of LTBP2 in the microfibril formation of mouse embryonic fibroblasts [ 82 ]. Furthermore, LTBP4 genetic mutations have been linked to various disorders, including cutis laxa [ 81 , 83 , 84 , 85 ], scleroderma [ 81 , 86 ], pulmonary [ 81 , 87 , 88 , 89 ], cardiac [ 81 , 90 , 91 , 92 ], and cancer [ 81 , 93 , 94 ]. Our group reported that both TGF-β1 and TGF-β3 modulated LTBP1 expression, but only TGF-β3 modulated LTBP2 expression in 3D HCF constructs.…”
Section: Discussionmentioning
confidence: 99%